Fracture Mechanics: 26th Volume 1995
DOI: 10.1520/stp16386s
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional CTOA and Constraint Effects During Stable Tearing in a Thin-Sheet Material

Abstract: A small strain theory, three-dimensional elastic-plastic finite element analysis was used to simulate fracture in thin sheet 2024-T3 aluminum alloy in the T-L orientation. Both straight and tunneled cracks were modeled. The tunneled crack front shapes as a function of applied stress were obtained from the fracture surface of tested specimens. The stable crack growth behavior was measured at the spec&en surface as a function of applied stress. The fracture simulation modeled the crack tunneling and extension as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…This confirms an earlier review by Parks [28] and agrees with the results discussed in [20,30,31] where FE analyses were compared with CTOA or CTOD measurements.…”
Section: Comparison Of Observed Hrr and Fe Fieldssupporting
confidence: 91%
See 2 more Smart Citations
“…This confirms an earlier review by Parks [28] and agrees with the results discussed in [20,30,31] where FE analyses were compared with CTOA or CTOD measurements.…”
Section: Comparison Of Observed Hrr and Fe Fieldssupporting
confidence: 91%
“…Indeed, it has been increasingly understood in the past decade that surface measurements are affected by 3-D effects [28][29][30], and that caution must be exercised in analysis of experimental data. For instance, it has been shown that plane-stress approximations are not sufficient to fit experimental measures such as the crack-tip opening angle (CTOA) or the crack-tip opening displacement (CTOD) (which are the surface measurements of crack-tip loading that are the most commonly performed), whereas 3-D analyses yield much better agreement [20,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTOA is than the angle enclosed by the upper and lower lines, L 1 and L 2 . A special case of optical measurement is the digital image correlation method [39,[41][42]. In [43] the authors, following earlier attempts, use a digital camera technique for investigating relatively tough pipeline materials.…”
Section: (A) Optical Microscopymentioning
confidence: 99%
“…Krytyczny kąt rozwarcia szczeliny jest jedynym parametrem tego kryterium. Kryterium CTOA zostało z powodzeniem zaimplementowane w obliczeniach wytrzymałości resztkowej połączeń nitowych [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Większość z prezentowanych wyników obliczeń była uzyskana przy pomocy programu FRANC3D współpracu-jącego z komercyjnym solwerem STAGS.…”
Section: Wstępunclassified